Consumers’ willingness to buy meat and seafood products close to the expiry date: an exploratory study from Denmark - Pandey, Sujita; Bohl, Amanda; Favari, Vittoria; Mora, Pietro; Phuyal, Sudikshya; Sojková, Eliška; Budhathoki, Mausam; Thomsen, Marianne (Frontiers in Nutrition, 2024)
Meat-and seafood-products close to their expiry date (MSPCED) are one of the significant contributors to the growing food waste. Therefore, this study aims to investigate consumers´ attitudes and willingness to buy MSPCED. An online questionnaire was used to collect data from 400 Danish consumers. Three consumer segments were identified based on their willingness to buy MSPCED: 39.8 % of the participants showed a high willingness to buy MSPCED close to their expiry date ("All High"), 34.5 % were selective with a high willingness to buy meat close to their expiry date but not seafood ("High meat, low seafood"), while 25.7% showed a low willingness to buy MSPCED ("All Low"). Consumers' willingness to buy MSPCED is influenced by the perceived quality of the products, food safety, social acceptability, and price. Consumers were willing to pay a higher price for minced beef close to the expiry date when compared to cod fillets, pork cuts, and chicken breasts. However, consumers were willing to buy cod fillets with the lowest discount percentage when compared to pork cuts, minced beef, and chicken breast. The findings suggest that price reduction and discount percentage can have varying effects in influencing willingness to pay for MSPCED. This study provides valuable insights, for food waste practitioners in the retail sector, to develop effective strategies for reducing food waste by influencing consumer willingness to buy and pay for perishable products like meat and seafood.